Teacher education modules for multi-grade teaching; draft - Commonwealth Secretariat, Human Resource Development Division, Education Development (Commonwealth Secretariat, 1997)
These eight modules, which were prepared by practicing teacher educators in the Caribbean are intended to assist in the training of teachers for multi-grade teaching, and also for use by classroom teachers. The modules presented are: Module 1: Multi-grade Teaching; Module 2: Timetabling; Module 3: Scheduling, Lesson Planning and Teaching Strategies; Module 4: Classroom Organization; Module 5: Grouping; Module 6: Curriculum; Module 7: Resources and Resource Management; and Module 8: Measurement and Evaluation.
Keywords: teacher education